Equivalence Translation in The Adam Project Subtitles - Putu Pradnyani Widyasari; Hikmaharyanti, Putu Desi Anggerina (Kajian Linguistik dan Sastra, 2025)
Translation requires accuracy and equivalence meaning according to the context and original expressionmeaning of a movie such as language nuances, idiomatic expressions, and cultural terms contained inthe movie. As a translator, it is important to have a better understanding of the translation procedureto ensure the quality and accuracy of the translation. This study aims to ensure the accuracy of theequivalence translation procedure used in the utterances of The Adam Project movie. English toIndonesian subtitles is the highlight of data collection. This study uses qualitative method focusing onequivalence translation procedure. The data are collected by selecting the equivalence translation onthe movie subtitles. The result shows that 27 utterances are identified as equivalence translationprocedure. The utterances of equivalence mostly use idiomatic expression in the source language andwhen they are translated into the target language, they can achieve the same meaning as in the sourcelanguage even though they are rendered unidiomatically.